Technology and the good life? - Higgs, Eric, 1958-; Light, Andrew, 1966-; Strong, David, 1955- (University of Chicago Press, 2000)
'Technology and the Good Life?' uses a careful collective analysis of Albert Borgmann's controversial and influential ideas as a jumping-off point from which to address questions about the role and significance of technology in our lives. Contributors both sympathetic and critical examine Borgmann's work, especially his 'device paradigm'; apply his theories to new areas such as film, agriculture, design, and ecological restoration; and consider the place of his thought within philosophy and technology studies more generally.